2016
DOI: 10.4306/pi.2016.13.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Times to Discontinue Antidepressants Over 6 Months in Patients with Major Depressive Disorder

Abstract: ObjectiveThe aim of the present study was to investigate differences in discontinuation time among antidepressants and total antidepressant discontinuation rate of patients with depression over a 6 month period in a naturalistic treatment setting.MethodsWe reviewed the medical records of 900 patients with major depressive disorder who were initially prescribed only one kind of antidepressant. The prescribed antidepressants and the reasons for discontinuation were surveyed at baseline and every 4 weeks during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…The high rate of discontinuation in our study is consistent with the high discontinuation rate reported in a recent study by Jung et al [ 24 ]. In this study, over 70% of patients discontinued antidepressants after 6 months (including patients who switched).…”
Section: Discussionsupporting
confidence: 93%
“…The high rate of discontinuation in our study is consistent with the high discontinuation rate reported in a recent study by Jung et al [ 24 ]. In this study, over 70% of patients discontinued antidepressants after 6 months (including patients who switched).…”
Section: Discussionsupporting
confidence: 93%
“…По эпидемиологическим данным, только у 40-50% пациентов имеется клинический ответ на принимаемый антидепрессант [7]. Согласно руководству терапии аффективных расстройств, длительность приема антидепрессантов должна составлять не ме-нее 1 года [7,10]. При этом пациенты могут длительное время принимать назначенный им препарат, однако, его эффект может быть незначительным или вообще отсутствовать.…”
Section: Using the Quantitative Eeg Methods In Predicting The Responseunclassified
“…Before the patient is “labeled” treatment-resistant, an attempt to optimize the IAD trial is essential by ensuring that the maximum recommended dose for the recommended duration has been used. A trial duration of approximately 4 to 6 weeks is recommended by most of the guidelines for the treatment of depression [ 12 , 13 ]. Results from the sequenced treatment alternatives to relieve depression (STAR*D) trial indicated that a longer trial period may be required for treated patients to develop the full therapeutic potential of the intervention.…”
Section: Introductionmentioning
confidence: 99%